2017
DOI: 10.1186/s12941-017-0251-8
|View full text |Cite
|
Sign up to set email alerts
|

Intensive care antibiotic consumption and resistance patterns: a cross-correlation analysis

Abstract: BackgroundOver recent decades, a dramatic increase in infections caused by multidrug-resistant pathogens has been observed worldwide. The aim of the present study was to investigate the relationship between local resistance bacterial patterns and antibiotic consumption in an intensive care unit in a Romanian university hospital.MethodsA prospective study was conducted between 1st January 2012 and 31st December 2013. Data covering the consumption of antibacterial drugs and the incidence density for the main res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 26 publications
2
33
0
3
Order By: Relevance
“…Although we noticed a decrease in cephalosporin use in 2016, the use of the 3rd generation cephalosporins was constant over the study period. Our results are in accordance with studies from other countries, where cephalosporins were the most frequently used antibiotics in hospitals, ranging from 30% in Chinese tertiary hospitals to 57% in Turkish hospitals [19][20][21]. Reports of antibiotic consumption in European hospitals during 2011-2015 showed that consumption of cephalosporins and other beta-lactams included carbapenems ranged from 7% in the United Kingdom to 54% in Bulgaria [22].…”
Section: Discussionsupporting
confidence: 91%
“…Although we noticed a decrease in cephalosporin use in 2016, the use of the 3rd generation cephalosporins was constant over the study period. Our results are in accordance with studies from other countries, where cephalosporins were the most frequently used antibiotics in hospitals, ranging from 30% in Chinese tertiary hospitals to 57% in Turkish hospitals [19][20][21]. Reports of antibiotic consumption in European hospitals during 2011-2015 showed that consumption of cephalosporins and other beta-lactams included carbapenems ranged from 7% in the United Kingdom to 54% in Bulgaria [22].…”
Section: Discussionsupporting
confidence: 91%
“…46 There are studies in the literature that correlate the use and the length of colistin therapy with the increase in the prevalence of colonization and infections caused by strains having intrinsic resistance to colistin, such as Proteeae, Serratia marcescens, Pseudomonas mallei, and Burkholderia cepacia. 15,46 Such increased colistin use was also noted in our hospital, 17,47,48 which may explain the increased incidence of infections with Proteeae.…”
Section: Discussionsupporting
confidence: 60%
“…The link between the prevalence of carbapenem-resistant P. aeruginosa isolates and carbapenem use is not novel. 1219 However, this current study shows that publicly accessible datasets can jointly be analysed and that such associations can be monitored in a longitudinal manner. For instance, the Japanese government has started to financially subsidize healthcare facilities in which antimicrobial stewardship teams (ASTs) are organized and actively engaged in regulating the use of antimicrobial agents.…”
Section: Discussionmentioning
confidence: 93%